An evaluation of the periodical collection and its use in the Lung Center of the Philippines Medical Library - Torres, Ma. Crineza B.; Carcellar, Marie Desiree R. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2007)
The medical library assumes increasing importance in providing quality library and information services to support and enhance the medical hospital. With the fast pacing of technology in the medical field, this study was conducted to determine the periodical collection of the Lung Center of the Philippines medical library and its compliance with the Brandon/Hill selected list of print books and journals for the small medical library.
The descriptive research method was used for this study. The respondents were the doctors, nurses, and staff of the Lung Center of the Philippines medical library. Students from colleges and universities were also included because they visit the medical library to do their homeworks and research papers. Data gathered from the questionnaires were collated and analyzed with the aid of the Statistical Package for the Social Sciences (SPSS) software, using frequency distribution and percentages.
This study found out that the Lung Center of the Philippines medical library did not comply with the Brandon/Hill standards in terms of periodical collection for the reason that the said medical library did not reach 50 of the total core list of journals. The researcher, therefore, recommends that Brandon/Hill standards be used by the said medical library to keep pace with the latest developments and trends. The need to assess the perceptions of library users must be done more often, as well as regular evaluation of periodical collections to determine the success or failure of the library services.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Lung Center of the Philippines Medical Library; Medical libraries -- Evaluation. -- Philippines -- Quezon City -- Periodicals